Sorption behavior of cesium on silt and clay soil fractions. (July 2021) - Park, Chan Woo; Kim, Sung-Man; Kim, Ilgook; Yoon, In-Ho; Hwang, Juri; Kim, June-Hyun; Yang, Hee-Man; Seo, Bum Kyung
Abstract: The effect of clay mineral composition on Cs adsorption behavior of silt and clay fractions (SC-fractions) of soil was investigated. Surface soil samples were collected within 2 km of Kori and Wolsong nuclear power plants in South Korea, and SC-fractions (<20 μm) were separated. The physicochemical properties of SC-fractions and types of clay minerals contained in the SC-fractions were analyzed. The cesium adsorption capacity of the SC-fractions, and affinity between the SC-fractions and Cs, were investigated by isothermal adsorption analysis using the dual-site Langmuir adsorption model. To understand selective adsorption of Cs, the radiocesium interception potential and distribution coefficient of the SC-fractions were analyzed in the presence or absence of competing ions. The radiocesium distribution coefficient of the SC-fractions showed a trend similar to that of the Langmuir sorption coefficient of high-affinity binding sites for Cs in the SC-fractions. The SC-fractions of Kori soils that contain only non-expandable clay minerals including highly weathered mica had low Cs adsorption capacity. However, the SC-fractions of Kori soils showed higher Cs adsorption selectivity compared to the SC-fractions of Wolsong soils containing expandable clay minerals and micaceous mineral with a low degree of weathering. It is predicted that the highly weathered micas have high affinity to Cs, and such clay minerals contribute the most to the adsorption process in dilute solutions. Highlights: The Cs sorption behavior of silt and clay fractions of actual soil was investigated. The samples containing highly weathered mica showed a high Cs sorption selectivity. The dual-site Langmuir sorption model was applied to analyze heterogeneous Cs sorption. The Cs distribution coefficient and the Langmuir sorption coefficient of Cs selective sorption site showed a similar trend. The clay minerals that have high affinity to Cs contributed the most to the sorption process.